Elevated Temperature Strength Enhancement of ZrB2–30 vol% SiC Ceramics by Postsintering Thermal Annealing. Issue 3 (25th November 2015) - Neuman, Eric W.; Hilmas, Gregory E.; Fahrenholtz, William G.
Abstract : The mechanical properties of dense, hot‐pressed ZrB2 –30 vol% SiC ceramics were characterized from room temperature up to 1600°C in air. Specimens were tested as hot‐pressed or after hot‐pressing followed by heat treatment at 1400°C, 1500°C, 1600°C, or 1800°C for 10 h. Annealing at 1400°C resulted in the largest increases in flexure strengths at the highest test temperatures, with strengths of 470 MPa at 1400°C, 385 MPa at 1500°C, and 425 MPa at 1600°C, corresponding to increases of 7%, 8%, and 12% compared to as hot‐pressed ZrB2 –SiC tested at the same temperatures. Thermal treatment at 1500°C resulted in the largest increase in elastic modulus, with values of 270 GPa at 1400°C, 240 GPa at 1500°C, and 120 GPa at 1600°C, which were increases of 6%, 12%, and 18% compared to as hot‐pressed ZrB2 –SiC. Neither ZrB2 grain size nor SiC cluster size changed for these heat‐treatment temperatures. Microstructural analysis suggested additional phases may have formed during heat treatment and/or dislocation density may have changed. This study demonstrated that thermal annealing may be a useful method for improving the elevated temperature mechanical properties of ZrB2 ‐based ceramics.